MAPbBr3−xIx Crystals Improved by Accurate Solution-Grown Procedure for Alpha Particle Detection - Liu, Xin; Fu, Jinghua; Zhao, Dou; Hao, Yingying; Zhu, Hao; Xu, Meng; Zhang, Binbin; Jie, Wanqi; Xu, Yadong (Frontiers in Physics, 2020)
High quality organic-inorganic halide perovskite brings an opportunity for ideal nuclear radiation detection due to its large carrier mobility, lifetime and heavy atoms. However, the relatively low bulk resistivity restricts its development for alpha particles and X/γ-ray detector. Here, we report on the MAPbBr3-xIx (MPB:I) perovskite crystals grown by the modified inverse temperature crystallization method. Based on the measured supersolubility and solubility curves, the heating procedure was accurately designed to control the nucleation and growth rate. The resulting MPB:I single crystals exhibit higher bulk resistivity of 1.4×109 Ω·cm, which is 10 times than that obtained from the traditional ITC method. Finally, An uncollimated 0.8 μCi 241Am @5.48 MeV alpha particles source was adopted to evaluate the MPB:I single crystals at room temperature condition. The electron mobility (μe) and mobility-lifetime product (μτ)e of (264.6 ± 6.5) cm2 V-1 s-1 and (2.6 ± 0.3) × 10-3 cm2/V, respectively, were obtained.